Electrochemical impedance analysis and degradation behavior of a Ni-GDC fuel electrode containing single cell in direct CO2 electrolysis. (March 2023) - Unachukwu, Ifeanyichukwu D.; Vibhu, Vaibhav; Uecker, Jan; Vinke, Izaak C.; Eichel, Rüdiger-A.; (Bert) de Haart, L.G.J.
Abstract: The challenges of high degradation rate and significant carbon deposition, which are common with Ni-YSZ electrodes, have shifted attention to other electrode materials with enhanced performance in SOECs using carbon-containing fuels. In this study, the performance and electrochemical behavior of the Ni-GDC fuel electrode under CO2 electrolysis were investigated. The study was performed over a range of operating conditions, varying the operating temperature, the CO2 content of the fuel gas as well as the oxygen partial pressures in the oxygen electrode gas. Long-term stability test was performed up to 1070 h at 900 °C and a current density of − 0.5 A‧cm −2 . The electrochemical impedance spectra obtained from the various measurement were evaluated with DRT as well as an equivalent circuit model consisting of 4 time-constant; (LR-RQ1-RQ2-RQ3-Ws). The low frequency Warburg (short) element (Ws) was attributed to gas diffusion and surface processes at the fuel electrode, the mid frequency processes of RQ2 and RQ3 are assigned to the combined contribution of fuel and oxygen electrode. The high frequency RQ1 was assigned to the charge transfer process at the oxygen electrode. A low degradation rate of 31 mV‧Kh −1 was observed during the long-term stability test. Furthermore, analysis of the degradation rate illustrates that significant contributions to the degradation were from the mid and high frequency processes, in addition to ohmic resistance. SEM analysis of the measured cell shows agglomeration of Ni particles, increase in electrode porosity as well as Ni migration away from the electrode/electrolyte interface. Highlights: Direct CO2 electrolysis using single cell containing Ni-GDC fuel electrode. High current density of − 1.16 A‧cm −2 is obtained at 1.5 V and 900 °C for Ni-GDC cell. Low degradation rate of 33 mV‧Kh −1 is observed after long term operation. Ni particle migration, agglomeration and increase in electrode porosity are observed.